The reflection of diode technology light emitting (LED) on the modular design of external lighting (Al-Academy, 2017)
Search marked (the reflection of diode technology light emitting (LED) on the modular design of external lighting) is an analytical study of the units, external lighting for gardens and adopted in its work on the diode technology emitting light to reach the magnitude of the effect and the change happening where according to this technique was the problem of the research in which is (what emotion the formal and functional units of external lighting according diode technology light emitting) and identified in the first part of it, including the goals came Search of b (statement reversal winning technical transformation of lighting from incandescent bulbs to light emitting diode technology (LED) on each of shape design and the nature of the job performance of the units, external lighting), meaning that research was devoted to the purpose of the answer to a question for the formal and functional transformation units of external lighting operating principle of light emitting diode by showing the change in both form and function to those units, has identified research study those units from selected her models to show the difference .and to make a knowledge base the second part base theoretical research where literature for each of the units traditional lighting of various kinds and what respect diode technology emitting light in principle to his work and features collected, in addition to that dealt with the topic subject for verification Occupation Authority and lighting units discussed the relationship between function and body building and industrial products from units external lighting to determine the extent of the impact and influenced each of them according to that relationship. in the fourth section has identified research procedures and the select descriptive approach as a basis for access to the results through the study of selected samples is my intention in global models for the two companies competent so and so by analyzing each of them, which was in the fourth section, where those samples were analyzed to reach results in The fifth topic is the most important1. Forms of lighting units mimicked the image that the designer wanted to transfer to the recipient with a check function required of them